2021
DOI: 10.7759/cureus.16752
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Indices Predicting the Severity of Acute Pancreatitis Presenting to the Emergency Department: A Retrospective Analysis

Abstract: IntroductionAcute pancreatitis is defined as inflammation of the pancreas. The body responds to inflammation by producing excessive neutrophils and causing programmed cell death of lymphocytes. This leads to immunological instability, which increases the severity of the disease and mortality rate. Recent data suggest that markers of systemic inflammation are able to predict the prognosis of various diseases. Our study aims to assess the severity of acute pancreatitis in conjunction with these hematological mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This is also true for other inflammatory diseases such as acute pancreatitis and a better understanding of the role of the cells of the adaptative immune system in acute pancreatitis might have a huge impact on the outcomes and future treatments of patients with acute pancreatitis.The neutrophil-tolymphocyte ratio has been shown to be superior to white blood cell count in predicting adverse outcomes of acute pancreatitis [27]. Another study also showed that the neutrophil-to-lymphocyte ratio was related to acute pancreatitis severity [18]. The neutrophil-to-lymphocyte ratio has been shown to be a good indicator of severe disease in inflammatory diseases including sepsis and acute pericarditis.…”
Section: Discussionmentioning
confidence: 99%
“…This is also true for other inflammatory diseases such as acute pancreatitis and a better understanding of the role of the cells of the adaptative immune system in acute pancreatitis might have a huge impact on the outcomes and future treatments of patients with acute pancreatitis.The neutrophil-tolymphocyte ratio has been shown to be superior to white blood cell count in predicting adverse outcomes of acute pancreatitis [27]. Another study also showed that the neutrophil-to-lymphocyte ratio was related to acute pancreatitis severity [18]. The neutrophil-to-lymphocyte ratio has been shown to be a good indicator of severe disease in inflammatory diseases including sepsis and acute pericarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, lymphocyte-to-monocyte ratio (LMR) could serve as one of the predictive indices for persistent organ failure and mortality ( 70 75 ). Compared with mild AP (MAP; no organ failure, no local or systemic complications) or moderately severe AP (MSAP; transient organ failure or local or systemic complications) patients, those with severe AP (SAP; persistent organ failure) as defined by the revised Atlanta classification ( 76 ) had a lower LMR ( 71 , 73 , 74 , 77 , 78 ). Paradoxically, SAP patients with uncertain time of disease onset had reduced lymphocyte and monocyte counts at the early stage of their ICU stay, perhaps indicating an immune anergy later in severe disease, which recovered to normal on day 7 ( 79 ).…”
Section: Monocytes In Apmentioning
confidence: 99%
“…As in every period of inflammation, excessive neutrophils count are produced and cell death begins in the lymphocytes count. [1][2][3] Lymphocyte, neutrophil, and thrombocyte counts can be effective in the inflammation process as well as with the proportional indices between them, and they are also the subject of studies on many chronic inflammatory diseases since they are associated with the prognosis. [4,5] The neutrophil to lymphocyte ratio (NLR) was studied in relation to asthma, [7] chronic obstructive pulmonary disease (COPD), [8] and intensive care patients.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The neutrophil to lymphocyte ratio (NLR), neutrophil/lymphocyte*platelet ratio (NLPR), systemic inflammation response index (SIRI), and aggregate inflammation systemic index (AISI) were examined in patients diagnosed with thyroiditis, [4] rheumatoid arthritis, [5] and pulmonary fibrosis [6] in order to examine the post-operative inflammatory processes [10] even in patients diagnosed with COVID-19. [11][12][13] Although we know that the effects of hematological parameters on prognosis in patients with pancreatitis have been examined, [3,14] there was no pancreatitis study using hematological inflammatory indices other than NLR, [1,14] and related to the length of hospital stay, mortality, or intensive care hospitalization rates, as far as we can detect. The aim of the instant study is to evaluate the predictability of AISI, NLPR, and SIRI in patients with acute pancreatitis, which predicts more than 7 days of hospitalization, the need for intensive care, and 30-day mortality.…”
Section: Introductionmentioning
confidence: 99%